Fixed Point and Newton's Methods in the Complex Plane. (29th January 2018) - Dubeau, François; Gnang, Calvin
Abstract : We revisit the necessary and sufficient conditions for linear and high order of convergence of fixed point and Newton's methods in the complex plane. Schröder's processes of the first and second kind are revisited and extended. Examples and numerical experiments are included.